2023
DOI: 10.1186/s12870-023-04107-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the global diurnal rhythmic transcripts, transcription factors and time-of-day specific cis elements in Chenopodium quinoa

Abstract: Background Photoperiod is an important environmental cue interacting with circadian clock pathway to optimize the local adaption and yield of crops. Quinoa (Chenopodium quinoa) in family Amaranthaceae has been known as superfood due to the nutritious elements. As quinoa was originated from the low-latitude Andes, most of the quinoa accessions are short-day type. Short-day type quinoa usually displays altered growth and yield status when introduced into higher latitude regions. Thus, deciphering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…None of the genes found to be down-or up-regulated after NB by Wu et al (2021) (LHY, ELF3, HY5, PHYA , and CRY1) were differentially regulated in our study. However, CqFT2B and CqZTL, identified by Wu et al (2023) in a transcriptome study of diurnally collected samples under SD and LD, were also found in our study, which supports their role as flowering time regulators. Moreover, Patiranage et al (2021) provided additional evidence that CqFT2B's temporal and diurnal expression in early-and late-flowering quinoa accessions underpins its function as a flowering time regulator.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…None of the genes found to be down-or up-regulated after NB by Wu et al (2021) (LHY, ELF3, HY5, PHYA , and CRY1) were differentially regulated in our study. However, CqFT2B and CqZTL, identified by Wu et al (2023) in a transcriptome study of diurnally collected samples under SD and LD, were also found in our study, which supports their role as flowering time regulators. Moreover, Patiranage et al (2021) provided additional evidence that CqFT2B's temporal and diurnal expression in early-and late-flowering quinoa accessions underpins its function as a flowering time regulator.…”
Section: Discussionsupporting
confidence: 89%
“…(2021) ( LHY, ELF3 , HY5 , PHYA , and CRY1 ) were differentially regulated in our study. However, CqFT2B and CqZTL , identified by Wu et al . (2023) in a transcriptome study of diurnally collected samples under SD and LD, were also found in our study, which supports their role as flowering time regulators.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations